Sex, dating and delinquency: do precocious relationships lead to crime? - Kierkus, Christopher A. (Criminal justice recent scholarship, 2009)
Opposite sex relationships and delinquent behavior -- Precocious transitions and gender differences in offending -- An empirical investigation of the links between early dating and delinquent behavior -- Results : early relationships and delinquent behavior -- Conclusions : do early relationships lead to delinquent behavior